Effect on plaque control in children patients with Down syndrome using Digital Brush with or without chlorhexidine: a randomized clinical trial. (29th December 2015) - Stefanini, Martina; Sangiorgi, Matteo; Roncati, Marisa; D'Alessandro, Giovanni; Piana, Gabriela
ABSTRACT: Objectives: The aim of this study was to evaluate efficacy in children affected by Down syndrome of "Digital Brush" in terms of Plaque Index reduction added to the daily oral hygiene procedures. Methods: A total of 56 patients with Down syndrome were recruited and randomly assigned in two groups: both control and test groups underwent standard hygiene procedures of tooth brushing twice a day followed by the intervention of Digital Brush, TNT gauze impregnated with chlorhexidine 0.12%, for the test group and by sterile gauze soaked in water for the control group. Initial plaque index was measured for all patients (T0), subsequently were instructed to use either Digital Brush or gauze soaked with water for 2 weeks. At last, patients were reevaluated (T1) and the plaque index measured. Results: Plaque index improvement from T0 to T1 in control group was 11.7%, while in test group was 24.1%. The mean differences between test and control group was statistically significant ( p < 0.001). Conclusions: This study demonstrates how the Digital Brush, added to the daily oral hygiene procedures, obtains significant improvements in supragingival plaque control in children with Down syndrome.